2007
DOI: 10.1130/g23495a.1
|View full text |Cite
|
Sign up to set email alerts
|

Plutonic xenoliths reveal the timing of magma evolution at Hualalai and Mauna Kea, Hawaii

Abstract: Hawaiian volcanoes evolve through stages that have been delimited by the compositions of their erupted lavas. New in situ 238 U-230 Th and U-Pb dating of single zircons from leucocratic plutonic xenoliths erupted at Mauna Kea and Hualalai volcanoes, Hawaii, reveals that important episodes of magmatic evolution are not necessarily refl ected in the stratigraphy or compositions of erupted lavas. Zircons from Mauna Kea diorites form a heterogeneous population with apparently bimodal ages of ca. 125 ka and ca. 65 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…A similar result can be obtained by magma replenishment and mixing with residual phases of older silicic magma chambers (Brown and Fletcher, 1999). Vazquez et al (2007) have also shown that coeval evolution of chemically distinct magma reservoirs characterized alkalic magma generation in Hawaii. In addition, as concluded by Simon et al (2007), it is unlikely that volcanism could erupt from a single long-lived magma chamber: rather there would be an episodic record with different magmas.…”
Section: Interpretation Of the Ages And Magma Residence Timesupporting
confidence: 62%
See 1 more Smart Citation
“…A similar result can be obtained by magma replenishment and mixing with residual phases of older silicic magma chambers (Brown and Fletcher, 1999). Vazquez et al (2007) have also shown that coeval evolution of chemically distinct magma reservoirs characterized alkalic magma generation in Hawaii. In addition, as concluded by Simon et al (2007), it is unlikely that volcanism could erupt from a single long-lived magma chamber: rather there would be an episodic record with different magmas.…”
Section: Interpretation Of the Ages And Magma Residence Timesupporting
confidence: 62%
“…CAMECA 1270, Schmitt et al, 2003; or SHRIMP, see Compston et al, 1982). It has been demonstrated that zircon as young as 1 Ma and even less can also be dated (for instance, Brown and Fletcher, 1999;Bacon et al, 2000;Vazquez et al 2007 have given reliable ages of about 340, 100 and 300 ka, respectively). Recently, an alternative method has emerged that employs MC-ICPMS (Multi Collector Inductively Coupled Plasma Mass Spectrometer) together with laser ablation Cocherie and Robert, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…These data suggest that the magma system at Veniaminof was producing evolved, vapour-rich melts at the same time as it was erupting basalt to basaltic andesite (Bacon et al 2007). At Hualalai, Hawaii, ages of zircon in syenogabbros and diorites document the presence of alkalic magmas in the subvolcanic reservoir system more than 120 kyr before the surface tholeiitic to post-shield alkalic transition (Vazquez et al 2007). This suggests that Hualalai, like Mauna Kea, had a protracted tholeiitic to alkalic transition but that only some of it was recorded in the erupted magmas.…”
Section: Plutons and Plutonic Blocks In Volcanic Rocksmentioning
confidence: 90%
“…Interpretation of plutonic lithics requires care as they may originate from different stages of the magmatic evolution of a volcano: (1) magma crystallized along the carapace during previous episodes of eruption (Charlier et al 2003;Bacon and Lowenstern 2005;Bachmann 2010), (2) an earlier solidified or chemically distinct injection of magma into the shallow crust that is unrelated to active rhyolite formation (Keller 1969;Lowenstern et al 2000;Charlier et al 2003;Vazquez et al 2007), or (3) a solidified portion of a cumulate crystal mush (Burt et al 1998). Thus, we first establish the origin and timing of formation of the TVZ plutonic lithics before using them to interpret the magma chamber processes.…”
Section: Introductionmentioning
confidence: 99%